Quick Response Code Attendance System for Congregational Activity on Android-based Platform: Aplikasi Presensi Kehadiran Kegiatan Jemaat Menggunakan Sistem Quick Response Code berbasis Android - Christian Cleavy Sunkudon; Xaverius B. N. Najoan; Sherwin R. U. A. Sompie (Jurnal Teknik Informatika, 2023)
Abstract — Evolution and life in modern times are developing rapidly, marked by the presence of technology such as smart mobile devices or smartphones and information technology today. Developments in modern times also have an impact on church life, one of which is the development of information technology. The management of information technology for the church is of particular concern in the life of the church ministry. One of the problems that occurs is the limited information resources of the congregation because the platform for this is not yet available. It was also found that the administration of attendance data collection for congregational activities still uses traditional methods that are less effective. In connection with the problems described above, it is necessary to breakthrough the management of data information from the old ways to a more systematic and modern process that can be used by the church, especially for the congregation iteself. This research aims to make changes in data management systems for the church, in the form of platforms that can be accessed by the congregation. Where this platform can accommodate congregation information, and can be accessed using existing mobile devices. The presence of information technology innovation by utilizing quick response system technology, helps various fields related to data, one of which is attendance recording. Congregations can use this platform to get access to information from the church. By using the Rapid Application Development method approach, this platform was successfully created as an innovation in church ministry. The result is a platform that is able to manage congregation data, as well as a place to record church attendance, without worrying about data inconsistencies. This platform is expected to be a new forum for church services and increase efficiency and ease of data access for church community layers. Key words—Android; Church; QR; Platform